Impact socio-économique de l’aménagement hydro-rizicole de Guiguidou dans la sous-préfecture de Divo (Côte d’Ivoire) - Joachim Koffi Kotchi; Yagnama Rokia Ouattara-Coulibaly; Guillaume Kouassi N’guessan (EchoGéo)
The present study aims to present the socio-economic impact of the project on the living conditions of the profit populations. The method used is based on a quantitative approach through questionnaires addressed to the recipients, to the managers in the operational one (MATAC-Chinese, the ONDR and the ANADER) and a qualitative approach which relates to the talks semi-directives, collective talks (focus group). The analysis of the data collected shows the recipients had access to farming novel methods and the socio-economic impact is remarkable with job creation. However, one belongs to many difficulties related to land, with the internal management of the project, which could compromise the durability of this participative local development model.